Buffer and Salt Effects in Aqueous Host-Guest Systems: Screening, Competitive Binding, or Both? - Jordan, Jacobs H.; Ashbaugh, Henry S.; Mague, Joel T.; Gibb, Bruce C. (Journal of the American Chemical Society, 2021)
There are many open questions regarding the supramolecular properties of ions in water, a fact that has ramifications within any field of study involving buffered solutions. Indeed, as Pielak has noted (Buffers, Especially the Good Kind, Biochemistry, 2021, in press. DOI:10.1021/acs.biochem.1c00200) buffers were conceived of with little regard to their supramolecular properties. But there is a difficulty here; the mathematical models supramolecular chemists use for affinity determinations do not account for screening. As a result, there is uncertainty as to the magnitude of any screening effect and how this compares to competitive salt/buffer binding. Here we use a tetra-cation cavitand to compare halide affinities obtained using a traditional unscreened model and a screened (Debye-Huckel) model. The rule of thumb that emerges is that if ionic strength is changed by >1 order of magnitude-either during a titration or if a comparison is sought between two different buffered solutions-screening should be considered. We also build a competitive mathematical model showing that binding attenuation in buffer is largely due to competitive binding to the host by said buffer. For the system at hand, we find that the effect of competition is approximately twice that of the effect of screening (similar to RT at 25 degrees C). Thus, for strong binders it is less important to account for screening than it is to account for competitive complexation, but for weaker binders both effects should be considered. We anticipate these results will help supramolecular chemists unravel the properties of buffers and so help guide studies of biomacromolecules.